A unified approach to transient stability contingency filtering, ranking and assessment. - Ernst, D. (IEEE Transactions on power systems)
This paper proposes a unified approach to contingency filtering, ranking and assessment in power system transient stability studies. The approach consists of two-block techniques in which the first block selects from a list of contingencies the a priori ?interesting? ones, that the second block ranks and assesses. This filtering, ranking and assessment (FILTRA) approach relies on SIME (for Single Machine Equivalent). SIME is a hybrid direct-time-domain stability method which combines accuracy and flexibility skills of time-domain methods with sound additional possibilities of direct methods. The FILTRA approach is fully general: it may adapt itself to the specifics of any power system (modeling, protection characteristics, etc.), any contingency scenario and mode of (in)stability (first- or multi-swing, local or inter-area mode) and any application context (planning, operation planning and real-time operation). The approach is illustrated on two EHV power systems, having different structures, control and protective devices. The adequacy of its filtering and ranking capabilities is illustrated in terms of performance criteria such as reliability (ability to consistently capture all dangerous contingencies), effectiveness (ability to avoid false alarms) and computational efficiency (ability to comply with real-time requirements). Further, the assessment task is shown to provide the operator with sound information and effective means of control